2021
DOI: 10.1016/j.ijid.2021.03.063
|View full text |Cite|
|
Sign up to set email alerts
|

Use of antibiotics is associated with worse clinical outcomes in patients with cancer treated with immune checkpoint inhibitors: A systematic review and meta-analysis

Abstract: Observational and experimental studies suggest that the use of antibiotics close to administration of immune checkpoint inhibitors (ICI) can have a negative effect on tumour response and patient survival, due to microbiome dysbiosis and the resultant suppression of host immune response against neoplastic cells. Methods: A systematic search of PUBMED and EMBASE was undertaken for studies published between 1 January 2017 and 1 June 2020, evaluating the association between the use of antibiotics and clinical outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 69 publications
(87 reference statements)
1
28
0
1
Order By: Relevance
“…Clarithromycin may potentiate the effect of tyrosine kinase inhibitors in chronic myeloid leukemia [ 19 ]. Anticancer properties of amoxycillin have not been reported, and antibiotic treatment may cause adverse changes in gut microbiota and is associated with the decreased efficacy of cancer immunotherapy [ 18 , 20 ]. Thus, we have no basis to presume that the antimicrobial treatment received by Patient 2 contributed to the tumour regression.…”
Section: Discussionmentioning
confidence: 99%
“…Clarithromycin may potentiate the effect of tyrosine kinase inhibitors in chronic myeloid leukemia [ 19 ]. Anticancer properties of amoxycillin have not been reported, and antibiotic treatment may cause adverse changes in gut microbiota and is associated with the decreased efficacy of cancer immunotherapy [ 18 , 20 ]. Thus, we have no basis to presume that the antimicrobial treatment received by Patient 2 contributed to the tumour regression.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of antibiotic therapy and its impact on immunotherapy efficacy ✩ To the Editor, We read with interest the meta-analysis by Tsikala-Vafea et al on whether antibiotic courses are associated with poorer clinical outcomes among cancer patients treated with immune checkpoint inhibitors (ICI) ( Tsikala-Vafea et al, 2021 ). Based on the hypothesis of antibiotic-induced gut dysbiosis, which could decrease ICI efficacy, this challenging question has a practical impact on patient care.…”
Section: Letter To the Editormentioning
confidence: 99%
“…Ahmed et al retrospectively compared ICI responses in patients who received broad-spectrum antibiotics including 3rd or 4th generation cephalosporins and ciprofloxacin with those who received no broad-spectrum ones within 2 weeks before and after starting ICI therapy and demonstrated that broad-spectrum antibiotics were associated with worse progression-free survival and overall survival in ICI therapy [ 44 ]. A recent systematic review and meta-analysis including 48 studies also indicated negative impacts of antibiotic use on overall survival, progression-free survival, response to treatment rate, and progression of disease [ 45 ]. Further studies will be required to determine how best to administer antibiotics to patients who will be treated or are undergoing treatment with ICIs including optimal timing, duration, and antibiotic types.…”
Section: Introductionmentioning
confidence: 99%